2015
DOI: 10.3791/52614
|View full text |Cite
|
Sign up to set email alerts
|

3D Organotypic Co-culture Model Supporting Medullary Thymic Epithelial Cell Proliferation, Differentiation and Promiscuous Gene Expression

Abstract: Intra-thymic T cell development requires an intricate three-dimensional meshwork composed of various stromal cells, i.e., non-T cells. Thymocytes traverse this scaffold in a highly coordinated temporal and spatial order while sequentially passing obligatory check points, i.e., T cell lineage commitment, followed by T cell receptor repertoire generation and selection prior to their export into the periphery. The two major resident cell types forming this scaffold are cortical (cTECs) and medullary thymic epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Several strategies have been developed to study the functional thymic properties, including ex vivo reaggregation thymic organ culture (RTOC) [19, 20], 2D mTEC-thymocyte adhesion [17, 18], transwell thymocyte migration [29], 3D fetal thymus organ culture (FTOC) [30], and 3D organotypic culture [23]. Considering that the 3D intrathymic environment is necessary for the development of a functional thymus scaffolding, development of thymic epithelial cells, chemoattraction of pro-T-cells, commitment to the T lineage, and generation of a repertoire of T-cell receptors (TCR) and natural T regulatory cells [31-33], an adequate thymus structure is mandatory to functionality study mTEC-mTEC interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several strategies have been developed to study the functional thymic properties, including ex vivo reaggregation thymic organ culture (RTOC) [19, 20], 2D mTEC-thymocyte adhesion [17, 18], transwell thymocyte migration [29], 3D fetal thymus organ culture (FTOC) [30], and 3D organotypic culture [23]. Considering that the 3D intrathymic environment is necessary for the development of a functional thymus scaffolding, development of thymic epithelial cells, chemoattraction of pro-T-cells, commitment to the T lineage, and generation of a repertoire of T-cell receptors (TCR) and natural T regulatory cells [31-33], an adequate thymus structure is mandatory to functionality study mTEC-mTEC interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Two experimental strategies enable the study of the in vitro formation of the thymus’s 3D structure that reproduces its microenvironment with the extracellular matrix and thymic epithelial cells. One of these strategies is the thymus re-aggregation [19, 20], and the other is the 3D organotypic culture [23]. In the re-aggregation model, the thymus tissue is devoid of cells (decellularized).…”
Section: Introductionmentioning
confidence: 99%
“…To create the dermal equivalent (DE), human fibroblasts were cultured on a viscose fiber fabric, that was punched in circles of 11mm in diameter and autoclaved in advance. These constructs grew in 12-well plates with hanging inserts in DMEM medium (4g glucose/l//Ham’s F12: 1:1 (500 mL + 500 mL), 10% FCS, 2% Pen/Strep, hydrocortisone (400 µg/L), ascorbic acid (50 µg/mL), aprotinin (250 E/mL)) [ 24 , 25 , 26 ] for up to 14 days prior to tumor cultivation, allowing fibroblasts to produce extracellular matrix and hence form solid tissue matrices (DEs).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, thymus transplantation and in vitro bioengineering can either be utilized to boost the recovery of thymic function or treatment of patients with congenital thymic atrophy ( 184 ). The most commonly used method is the transplantation of artificial thymic stromal cells, mainly thymic epithelial progenitor cells (TEPC), containing intercellular interaction components to support T cell development ( 185 ). Studies of animal models have demonstrated that, via an in vitro reprogramming technique, TEPC can induce human embryonic stem cells to form TEC and then transplant them into mice under the regulation of FOXN1, IL-7 ( 130 , 156 ), BMP4 ( 78 ), FGF and EGF to form thymus structure ( 155 , 185 ).…”
Section: Regeneration Strategies Of the Thymusmentioning
confidence: 99%
“…The most commonly used method is the transplantation of artificial thymic stromal cells, mainly thymic epithelial progenitor cells (TEPC), containing intercellular interaction components to support T cell development ( 185 ). Studies of animal models have demonstrated that, via an in vitro reprogramming technique, TEPC can induce human embryonic stem cells to form TEC and then transplant them into mice under the regulation of FOXN1, IL-7 ( 130 , 156 ), BMP4 ( 78 ), FGF and EGF to form thymus structure ( 155 , 185 ). Another method is to remove all the thymus cells and leave only the matrix components, which can be recombined with artificial thymic stromal cells and T lymphoid progenitor cells to form functional thymus ( 186 ).…”
Section: Regeneration Strategies Of the Thymusmentioning
confidence: 99%